Factors affecting access to finance for small and medium-sized agricultural enterprises in Vietnam - Huong, Dao Thi; Anh, Nguyen The (Asian Economic and Financial Review, 2024)
This study explores the financial accessibility challenges faced by small and medium-sized enterprises (SMEs) in Vietnam’s agricultural sector, a critical component of the national economy. This study reveals the various obstacles that hinder small and medium enterprises (SMEs) from accessing financial assistance. It highlights the need to have a thorough comprehension of how factors such as financial infrastructure, government laws, risk management, market connections, and financial literacy impact SMEs’ ability to access finance. The research suggests that enhancing financial literacy, along with developing a solid financial infrastructure and supportive government policies, is crucial for SMEs. It highlights the importance of tailored banking services, strategic government actions, effective risk management, and integration into market linkages to improve SMEs’ financial inclusion. The findings advocate for a holistic approach to address these challenges, offering insights for policymakers, financial institutions, and stakeholders in the SME ecosystem. The study offers practical guidance for enhancing the economic resilience of agricultural SMEs in Vietnam and other developing economies. It proposes strategies to strengthen financial infrastructure, support policies, and promote financial literacy. This study contributes valuable insights to both academic research and practical applications.